Síntese, cristalografia e atividade biológica de complexos triazenidos de Au(I), Ag(I), Pd(II) E Pt(II) - Locatelli, Aline (2012)
This work presents the synthesis of compounds and their triazenes complexes of gold(I), silver(I), platinum(II) and paladium(II). Triazenes have three nitrogen atoms connected in sequence [ N=N N(H) ] and, when deprotonated, they become excellent ligands in coordination chemistry. The synthesized ligands have ortho nitro substituent and variable substituent halogenated, or also in a position. Characterizations were performed using various techniques: thermogravimetric analysis, ultraviolet and visible spectroscopy, infrared and proton nuclear magnetic resonance, and the main focus of this work was the structural characterization of the complexes by X-ray diffraction on monocrystal, with emphasis the study of these supramolecular arrangements. Nitro and halide substituents (F, Cl, Br and I) providing the formation of various types of interactions, which form supramolecular arrangement. Four ligands were synthesized 1-(2-flurorphenyl)-3-(2-nitrophenyl)triazene (A), 1-(2-chlorophenyl)-3-(2-nitrophenyl)triazene (B), 1-(2-bromophenyl)-3-(2-nitrophenyl)triazene (C), 1-(2-iodophenyl)-3-(2-nitrophenyl)triazene (D) and thirteen complexes {[1-(2-fluorophenyl)-3-(2-nitrophenyl)triazenide](triphenilphosfine)gold(I)} (1), {[1-(2-chlorophenyl)-3-(2-nitrophenyl)triazenide](triphenilphosfine)gold(I)} (2), {[1-(2-bromophenyl)-3-(2-nitrophenyl)triazenide](triphenilphosfine)gold(I)} (3), {trans- bis-[1-(2-chlorophenyl)-3-(2-nitrophenyl)triazenide]-bis-(pyridine)paladium(II)} (4), {trans- bis-[1-(2-bromophenyl)-3-(2-nitrophenyl)triazenide]-bis-(pyridine)paladium(II)} (5), {trans- bis-[1-(2-iodophenyl)-3-(2-nitrophenyl)triazenide]-bis-(pyridine)paladium(II)} (6), {cis- bis-[1-(2-chlorophenyl)-3-(2-nitrophenyl)triazenide]-bis-(pyridine)platinum(II)} (7), {cis- bis-[1-(2-bromophenyl)-3-(2-nitrophenyl)triazenide]-bis-(pyridine)platinum(II)} (8), {cis- bis-[1-(2-iodophenyl)-3-(2-nitrophenyl)triazenide]-bis-(pyridine)platinum(II)} (9), {trans-[1-(2-bromophenyl)-3-(2-nitrophenyl)triazenide]-bis-(pyridine)(chloro)platinum(II)} (10), {cis- [1-(2-bromophenyl)-3-(2-nitrophenyl)triazenide]-ditriphenylphosfine(chloro)platinum(II)} (11), {bis-[1-(2-iodophenyl)-3-(2-nitrophenyl)triazenide]silver(I)} (12) e {[1-(2-fluorophenyl)-3-(2-nitrophenyl)triazenide](triphenylphosfine)silver(I)} (13). For the purpose of Bioinorganic studying the triazenido complexes of gold (I), and Platinum (II) were subjected to evaluation of biological activity shown promising results.